Traumatic Testicular Avulsion Following a Motorcycle Accident in Adolescent: A Case Report - Legie, Femmy Stefanie; Husein, Ali (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Traumatic testicular avulsion is a rare and severe urological emergency resulting from blunt scrotal trauma. It necessitates immediate diagnosis and surgical intervention. This case report describes the presentation and management of a complete testicular avulsion in an adolescent following a motorcycle accident.  A 15-year-old male was referred to Dr. Moewardi General Hospital after a motorcycle accident where he sustained a direct impact to his lower abdomen. Open wound on the right scrotum with complete detachment of the right testis, exposure of the spermatic cord, and irregular wound edges was found. The patient underwent emergency surgical exploration, which included debridement, ligation of the spermatic cord, and repair of the scrotal wound. The procedure was successful, and the patient was managed postoperatively with antibiotics and analgesics. Discussion: Testicular avulsion following a motorcycle accident is a urologic emergency. Management requires a multidisciplinary approach to address bleeding control, testicular function preservation, infection prevention, and scrotal reconstruction.